Conversion Therapy of Large Unresectable Hepatocellular Carcinoma With Ipsilateral Portal Vein Tumor Thrombus Using Portal Vein Embolization Plus Transcatheter Arterial Chemoembolization - He, Chengjian; Ge, Naijian; Wang, Xiangdong; Li, Hai; Chen, Shiguang; Yang, Yefa (Frontiers in Oncology, 2022)
Background: To assess the safety and efficacy of conversion therapy with portal vein embolization (PVE) and transcatheter arterial chemoembolization (TACE) in patients with large unresectable hepatocellular carcinoma (HCC) and ipsilateral portal vein tumor thrombus (PVTT) Methods: This retrospective study evaluated consecutive patients with initially large (≥5 cm) unresectable HCC with ipsilateral PVTT who underwent PVE + TACE at our center between June 2016 and September 2020 (Group A). Clinically equivalent patients from three centers who were receiving tyrosine kinase inhibitors (TKIs) + TACE (Group B) were included. The survival time were evaluated and compared between the two therapeutic groups. Results: In Group A (n=33), the median tumor diameter was 14 cm (range, 5–18 cm) and 19 (57.6%) patients underwent radical resection 18–95 days after PVE. Radical liver resection was not performed because of inadequate hypertrophy (n=11), pulmonary metastasis (n=1), lack of consent to surgery (n=1), and rupture of the HCC (n=1). There were no patients underwnt radical resection in Group B (n=64) (P =0.000). The mean and median overall survival (OS) were 736.5 days and 425.0 days in Group A and 424.5 days and 344.0 days in the Group B, respectively. Compared with TKIs + TACE, treatment with PVE + TACE prolonged OS (P = 0.023). Conclusions: This study shows that conversion therapy was safe and effective in patients with initially large unresectable HCC with ipsilateral PVTT treated with PVE + TACE. Moreover, PVE + TACE conferred more favorable outcomes than treatment with TKIs + TACE.